An Analysis of Pronouns Used by Informatic Engineering Students - Dewi, Hernalia Citra; Anggraeni, Dwinesa (STKIP PGRI Tulungagung, 2025)
The purpose of this study is to describe the types of pronoun usage in the descriptive text of 2nd semester students of Informatics study program. The approach method used is descriptive qualitative, while the techniques used for data collection are triangulated, and the analysis is inductive or qualitative. The results of the research conducted by the author show that there are 7 types of pronoun usage found in this study. . First, the use of personal pronouns as much as 7 or 30%. Second, the use of demonstrative pronoun as much as 1 or 4%. Third, the use of relative pronoun as much as 2 or 9%. Fourth, the use of possessive pronouns was 8 or 35%. Fifth, the use of reflexive pronouns as much as 2 or 9%. Sixth, the use of indefinite pronouns as many as 2 with a percentage of 9%. Seventh, the use of reciprocal pronoun was 1 with a percentage of 4%.